KETERLIBATAN INGGRIS DI KOTA LIMBANG SARAWAK SEBAGAI PEMICU KONFRONTASI INDONESIA-MALAYSIA - Yuwono, Ardi Tri; Ngasiman, Nur'irfaan Adrus bin; Ahad, Eizzah Bukhari binti (Historia, 2025)
Local history often receives little attention from the general public as well as historical researchers. However, local history has the ability to influence national history and even global history. One example of local history that has the potential to shape national history is the event that occurred on December 12, 1962 in the city of Limbang, Sarawak. This event became one of the triggers for the Indonesia-Malaysia Confrontation between 1963 and 1966, especially the involvement of the British in the city. This research aims to dig deeper into the role of the British in Limbang City on December 12, 1962. The method used in this study is a historical method with a qualitative approach. The British involvement in the city of Limbang on that date was to rescue the hostages captured by the TNKU (Tentara Nasional Kalimantan Utara). Most of the hostages were residents of Kampung Pemukat loyal to the Federation of Malaya and were kidnapped by groups that supported the incorporation of Sarawak, Brunei, and Sabah into Indonesia. The rescue action carried out by the British succeeded in freeing the prisoners in Limbang City on December 12, 1962, which resulted in a failure for the TNKU. The failure of the TNKU actually triggered tensions between Indonesia and Malaysia, which ultimately contributed to the Indonesia-Malaysia confrontation between 1963 and 1966.